1994
DOI: 10.1111/j.1365-2389.1994.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate sorption by synthetic amorphous aluminium hydroxides: a 27Al and 31P solid‐state MAS NMR spectroscopy study

Abstract: The sorption of phosphate on amorphous aluminium hydroxides was investigated using 27Al and P solid-state magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy, following the effect of different exposures to soluble phosphate. The spectra obtained were compared with the spectrum of amorphous aluminium phosphate. Aluminium i n the unreacted hydroxide had a 100% octahedral co-ordination. When dried at 200°C and exposed to soluble phosphate, very little (maximum 0.1 %) amorphous aluminium hydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 21 publications
4
64
0
Order By: Relevance
“…Beauchemin et al (2003) reported that Al-P was present only in the soil with the highest ammonium oxalate extractable Al content (673 mmol kg −1 ). The lack of detected Al-P by XANES in soils may result from its relatively low abundance due to inhibition of the formation of Al-P by Fe (hydr)oxides (Lookman et al, 1994). Khare et al (2004) reported that P preferentially adsorbed on ferrihydrite, with the adsorbed PO 4 concentration <100 mmol kg −1 (?3100 mg P kg −1 ) in a model system mixed ferrihydriteboehmite (1:1 mass ratio) suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…Beauchemin et al (2003) reported that Al-P was present only in the soil with the highest ammonium oxalate extractable Al content (673 mmol kg −1 ). The lack of detected Al-P by XANES in soils may result from its relatively low abundance due to inhibition of the formation of Al-P by Fe (hydr)oxides (Lookman et al, 1994). Khare et al (2004) reported that P preferentially adsorbed on ferrihydrite, with the adsorbed PO 4 concentration <100 mmol kg −1 (?3100 mg P kg −1 ) in a model system mixed ferrihydriteboehmite (1:1 mass ratio) suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…This slow uptake is thought to be the result of one or more of the following processes: i) diffusion to less accessible sites within pores of solid aggregates (Willet et al, 1988;Cabrera et al, 1981;Parfitt, 1989;Madrid and de Arambarri, 1985;Lookman et al, 1994); ii) penetration into the amorphous Fe and/or Al oxides by solid state diffusion (van Riemsdijk and de Haan, 1981;van Riemsdijk et al, 1984;Barrow, 1983); and iii) pre cipitation with metals derived by dissolution of the soil matrix (Aulenbach and Meisheng, 1988;Lookman et al, 1994;Martin et al, 1988;Nanzyo, 1984Nanzyo, , 1986Pierzynski et al, 1990). Malati et al (1993) reported that phosphate sorption on kaolinite, mica, and anatase at pH Ͻ 5 was endothermic and generally in the range of ϩ10 to ϩ15 kJ mol Ϫ1 .…”
Section: Phosphate Sorptionmentioning
confidence: 99%
“…The room temperature PLAMel5APP25C30B spectrum had one band centered at 8 ppm, which can be assigned to Al in octahedral coordination [25,26]. Another signal from the OMMT should be observed at 68 ppm corresponding to Al in tetrahedral coordination [25][26][27] but since the amount of OMMT is very low, that one is not observed. At 120 s the spectrum presents two peaks, a broad one at14ppm and second one which is low intense and broad at 8 ppm.…”
Section: Fig 6 13c Cp-dd-mas Nmr Spectra Of the Residues Of Plamelamentioning
confidence: 98%
“…Phosphoric acid (H3PO4) in aqueous solution (85 %) was used as a reference. 27 Al NMR measurements were carried out on the same spectrometer as above at 24.5 MHz (9.4 T) with MAS of 15 kHz). The repetition time was fixed at 1 s due to the quick relaxation time of the quadripolar nucleus, and a minimum of 1024 scans was necessary to obtain a satisfactory signal to noise ratio.…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation